A comparison of humanoid and non-humanoid robots in supporting the learning of pupils with severe intellectual disabilities - Aslam, Sarmad; Standen, Penny; Shopland, Nicholas; Burton, Andy; Brown, David (2016)
Previous research has shown that the humanoid NAO robot can enhance learning as well as improve communication in children with intellectual disabilities. However, most special needs schools cannot afford the humanoid NAO robot due to high costs. Could a cheaper nonhumanoid Lego Mindstorm robot be an alternative way of achieving the same learning objectives as the humanoid NAO robot? A single case study experimental ABAB design was used consisting of 16 sessions over 5 weeks: eight with the humanoid and eight with the non-humanoid robot. All sessions were video recorded and analysed for percentage engagement and percentage errors made by each of four students. For each student individually, these outcome measures were then compared between the two conditions. The teachers were interviewed at the end of the study. Three out of four students were significantly more engaged with the non-humanoid robot than the humanoid robot, whilst one student was found to be equally engaged with both robots. There was no significant difference between the two robots in terms of percentage errors for all four participants who managed to complete the study.